The corporate sustainability typology: analysing sustainability drivers and fostering sustainability at enterprises - Jerónimo Silvestre, Winston; Antunes, Paula; Leal Filho, Walter (Technological and Economic Development of Economy, 2018)
Much has been written about the need for more humane, ethical, socially just and transparent ways of doing business and performing entrepreneurial activities. Consistent with this, concepts such as sustainable development, corporate citizenship, corporate sustainability (CS), sustainable entrepreneurship, business ethics, and corporate social responsibility (CSR), among many others, have emerged. This diversity of expressions raises the need to development a new typology for to CS. This paper addresses this gap and describes a framework typology for corporate sustainability, by analysing sustainability drivers and the interactivity factors in the context of sustainability. It also describes the various types of sustainable emphasis given by companies and their associated levels of CS, which may pave the way for a new framework typology. First published online: 30 Nov 2016